2010
DOI: 10.1159/000319025
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade Internal Carotid Artery Stenosis and Chronic Brain Damage: A Volumetric Magnetic Resonance Imaging Study

Abstract: Background: Experimental data suggest that high-grade vascular stenosis may induce chronic cerebral tissue damage. Methods: We tested this hypothesis in 97 patients with a ≧70% unilateral internal carotid artery (ICA) stenosis (mean age: 69.1 ± 10.2 years), comparing intraindividual side-to-side differences in hemispheric brain and white matter hyperintensity (WMH) volumes. Patients with a supratentorial infarct exceeding 1.5 cm in diameter were excluded. Results: Overall, the median WMH volume was greater in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 55 publications
3
16
2
Order By: Relevance
“…The actual perfusion deficit can be underestimated from images taken of the posterior circulation [40]. Despite these limitations, our findings support the theory that carotid stenosis contributes to the pathogenesis of LA and that its elimination by CAS can reduce LA severity, suggesting the reversibility of ischemia-related LA [40]. It was shown that preoperative and postoperative LA scores depend on contralateral carotid stenosis and on whether the CoW is patent, and that LA responds to treatment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The actual perfusion deficit can be underestimated from images taken of the posterior circulation [40]. Despite these limitations, our findings support the theory that carotid stenosis contributes to the pathogenesis of LA and that its elimination by CAS can reduce LA severity, suggesting the reversibility of ischemia-related LA [40]. It was shown that preoperative and postoperative LA scores depend on contralateral carotid stenosis and on whether the CoW is patent, and that LA responds to treatment.…”
Section: Discussionsupporting
confidence: 73%
“…The location of the arterial input function can influence to some extent perfusion-weighted imaging. The actual perfusion deficit can be underestimated from images taken of the posterior circulation [40]. Despite these limitations, our findings support the theory that carotid stenosis contributes to the pathogenesis of LA and that its elimination by CAS can reduce LA severity, suggesting the reversibility of ischemia-related LA [40].…”
Section: Discussionsupporting
confidence: 72%
“…We used visual WML scores rather than lesion volumes but, while volumes can give a more sensitive measure of WML, they may be distorted by accidental inclusion of infarcts that have similar signal to WML [16]. Although possibly less sensitive, visual WML scores are more specific as they do not suffer from this and related problems due to artifacts, and scores and volumes are closely related [17].…”
Section: Discussionmentioning
confidence: 99%
“…Today, DSA is only rarely necessary—as opposed to the time when NASCET [3], ECST [4] and ACAS [5] were carried out. In addition to ultrasound, examinations such as CT and MR angiography allow collection of supplementary diagnostic insights, for example, perfusion studies, detection of vessel anomalies (aneurysms, angiomas), and plaque imaging, and can also be useful in cases where vessels are not well accessible via ultrasound or as an alternative investigation [26, 27]. …”
Section: Diagnostic Methodsmentioning
confidence: 99%